Influence of Maternal Age on the Relationship Between Endometrial Thickness and Ongoing Pregnancy Rates in Frozen–Thawed Embryo Transfer Cycles: A Retrospective Analysis of 2,562 Cycles - Tian, Haiqing; Zhang, Hejiang; Qiu, Hong; Yang, Xuejiao; La, Xiaolin; Cui, Lei (Frontiers in Endocrinology, 2022)
Background: In frozen–thawed embryo transfer (FET) cycles, endometrial thickness (EMT) has been used routinely as the main clinical monitoring index. However, the current findings are conflicting. Method: This was a single-center retrospective study of 2,054 couples (2,562 cycles) who underwent FET (including cleavage stage embryos and blastocysts) between January 2017 and August 2020 in the reproductive centers of First Affiliated Hospital of Xinjiang Medical University. The primary outcome measure was the ongoing pregnancy rate (OPR); the secondary outcome was the clinical pregnancy rate. Results: After stratified analysis and adjusting for confounders such as maternal age, duration of infertility, number of high-quality embryos transferred, endometrial preparation protocol, number of transfer cycles, and stages of embryo transferred, we found a curvilinear relationship between EMT and the OPR in women < 35 years of age. For women with EMT 8 mm, the OPR increased by 150% for cleavage stage embryo transfer for every 1 mm increase in the EMT; similarly, it increased by 97% for blastocyst stage FET. However, there was a linear relationship between EMT and OPR in women aged 35 years,When blastocysts were transferred, for every 1 mm increase in the EMT the OPR increased significantly by 12%. But OPR after frozen-thawed cleavage stage embryos transfer did not increase significantly with increased EMT Conclusions: Our study showed that the OPR increased significantly with increased EMT between young women aged < 35 years with EMT 8 mm and older women who underwent transfer of blastocysts.